Orbital maneuvers using gravitational capture times - Winter, O. C.; Neto, E. V.; Prado, AFBA (Elsevier B.V., 2003)
Artificial satellites around the Earth can be temporarily captured by the Moon via gravitational mechanisms., How long the capture remains depends on the phase space region where the trajectory is located. This interval of time (capture time) ranges from less than one day (a single passage), up to 500 days, or even more. Orbits of longer times might be very useful for certain types of missions. The advantage of the ballistic capture is to save fuel consumption in an orbit transference from around the Earth to around the Moon. Some of the impulse needed in the transference is saved by the use of the gravitational forces involved. However, the time needed for the transference is elongated from days to months. In the present work we have mapped a significant part of the phase space of the Earth-Moon system, determining the length of the capture times and the origin of the trajectory, if it comes from the Earth direction, or from the opposite direction. Using such map we present a set of missions considering the utilization of the long capture times. (C) 2003 COSPAR. Published by Elsevier B.V. Ltd. All rights reserved.